Cloud: Computing Services And Deployment Models (International Journal of Engineering and Computer Science, 2013)
Cloud computing is associated with a new paradigm for the provision of computing infrastructure and services. It represents a shift away from computing as a product that is purchased, to computing that is delivered as a service to consumers over the Internet from large scale data centers or clouds. Clouds provide an infrastructure for easily usable, scalable, virtually accessible and adjustable IT resources that need not be owned by an entity but can be delivered as a service over the Internet. The cloud concept eliminates the need to install and run middleware and applications on users own computer by providing Infrastructure, Platform and Services to users, thus easing the tasks of software and hardware maintenance and support. A cloud computing platform dynamically provisions, configures, reconfigures, and de-provisions servers as needed. Servers in the cloud can be physical machines or virtual machines. It was found that Cloud computing is changing the way we provision hardware and software for ondemand capacity fulfillment and changing the way we develop web applications and make business decisions